The secretion and retraction processes of pollination drops of ancient Platycladus orientalis and their response to different pollen types - Zhou, Wei; Gong, Liyan; Wang, Xiaobing; Li, Nawen; Zhang, Xin; Liu, Jianjun (Frontiers in Plant Science, 2025)
IntroductionThe pollination drop (PD) is an important ovular secretion that occurs during the pollination stage in gymnosperms.MethodsIn this study, ancient Platycladus orientalis trees near the Mausoleum of the Yellow Emperor were selected to investigate the secretion and retraction processes of PDs and the response of PDs to different pollen types.ResultsIn a natural setting, PDs were secreted in the early morning and retracted around noon, with the appearance time extending equally to both sides of 6 a.m., and there was a daily circadian rhythm of the variations. Similar changes were observed under in vitro conditions. Immediately after pollination, the PDs were retracted rapidly for a short time, after which the retraction rate gradually decreased for the next 20 min, and then remained almost unchanged, suggesting that there may be a comprehensive retraction mechanism for PDs. After pollination, the PD retraction rate decreased with decreasing pollen viability and botanical affinity, suggesting the presence of substances used for pollen identification, an identification mechanism and the presence of specific forms of identification or communication with pollen. The ability of the PDs of ancient P. orientalis trees to identify and respond to pollen increased with increasing tree age.DiscussionThe secretion and retraction of PDs may be two mutually exclusive processes that cannot be considered together. The younger the tree was, the stronger the driving force of secretion, as demonstrated by the higher PD secretion rate, larger surface area, and greater duration. The older the tree was, the stronger the driving force of retraction, as demonstrated by the significantly higher retraction rate of PDs after pollination. Each process has its own advantages and disadvantages in terms of pollination efficiency, but the decrease in the PD secretion rate by ancient P. orientalis was significantly lower than the increase in the PD retraction rate. In summary, female cones of older P. orientalis exhibit a greater reproductive ability than those of younger P. orientalis.